Frequency of canine degenerative myelopathy SOD1:c.118G>A mutation in 22 dog breeds in Guadalajara, Mexico - Ayala-Valdovinos, Miguel A.; Gómez-Fernández, Ana A.; Duifhuis-Rivera, Theodor; Aparicio-Cid, Eva A.; Sánchez-Chiprés, David R.; Galindo-García, Jorge (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Canine degenerative myelopathy (DM) is a late-onset disease that primarily affects large-breed dogs. The disease involves the spinal cord and produces progressive paresia and, eventually, complete loss of mobility. DM has been related to missense mutation c.118G>A in the SOD1 gene. Objective: To determine the genotypic and genic frequencies of DM in Mexico. Methods: In total, 330 samples from 22 different dog breeds were genotyped using the polymerase chain reaction and restriction fragment length polymorphisms (PCR-RFLP) technique. Results: The mutation was identified in 71 animals from 11 different breeds. Observed genic frequencies were 0.78 for the G allele and 0.14 for the A allele. Genotypic frequencies were 0.79 for the G/G wild-type, 0.14 for the G/A heterozygote, and 0.7 for the A/A homozygote. Conclusion: The genic frequency of this allele is high among the studied populations. A molecular marker program that identifies the DM mutation in breeding dogs should be implemented in order to reduce this frequency.